Impact of foreign aid and institutions on economic growth, income inequality and production efficiency - Saidon, Ruhaida (2015)
Five decades as humanitarian crises continue around the world, foreign aid remains as one of the important tools for the developed countries to improve standard of living in developing countries. The main goal of giving foreign aid is to alleviate poverty by generating economic growth in aid recipient countries. However, the empirical evidence on the effectiveness of foreign aid is inconclusive and has generated much controversial. Studies on aggregate foreign aid and institutional quality data indicated that the effectiveness of foreign aid is depend on the quality of institutions in aid recipient countries. This study attempts to examine the role of disaggregated institutions quality (i.e. socioeconomic condition, internal conflict, law and order, bureaucracy quality, ethnic tensions and investment profile) on the impact of sectoral allocations of foreign aid (i.e. aid to social sectors, aid to economic sectors, aid to production sectors and aid to multi sectors) on economic growth, income inequality and production efficiency in aid recipient countries during the period 1995 to 2009. This study used system-Generalized Method of Moment (sys- GMM) on a panel of 59 and 50 aid recipient countries in estimating the role of institutions quality on the impact of sectoral allocations of foreign aid on economic growth and income inequality, respectively. Meanwhile, the Data Envelopment Analysis (DEA) and panel Tobit regression on 80 recipient countries for the same period have been utilized in analyzing the role of disaggregated institutions quality on the impact of sectoral allocations of foreign aid on production efficiency in foreign aid recipient countries. The empirical results revealed that law and order has contingency effect on the relationship between sectoral allocations of foreign aid on economic growth, income inequality and production efficiency. These findings imply that law and order plays an important role as a complementary factor for the effectiveness of sectoral allocations of aid on enhancing economic growth, narrowing income inequality and increasing production efficiency in recipient countries. Moreover, empirical results also indicated that different sectoral allocations of foreign aid exerted different effects to economic growth, income inequality and production efficiency. Aid to production sector has significant impact on increasing economic growth. Oppositely, aid to economic and aid to social sectors have exhibited a negative impact on economic growth. However, aid to social sectors has exhibited a significant impact in reducing income inequality in the aid recipient countries. In addition, findings showed that aid to economic sectors is effective in increasing production efficiency in aid recipient countries. This study also determines the impact of disaggregated institutions quality on economic growth, income inequality and production efficiency in recipient countries. The empirical findings on the impacts of institutions quality reported that different institutions quality have different impacts on economic growth. income inequality and production efficiency. This study exposes that the quality of institutions such as socioeconomic condition, internal conflict and ethnic tensions are found to have a positive and significant impact on economic growth. In addition. bureaucratic quality has positive influence on production efficiency but it affected economic growth adversely. Meanwhile law and order is found to have positive and negative impact on production efficiency and income inequality, respectively. As long as different disaggregated institutions quality and sectoral allocations of foreign aid exerted different impacts on the development of recipient countries. international organization, such as World Bank, International Monetary Fund (IMF) and donor countries should provides foreign aid corresponding to the development objectives in the recipient countries. In addition, recipient countries should improve and maintain good quality of institutions in order to enhance the effectiveness of foreign aid.